Penegakan Hukum Penitensier Bagi Pelaku Kekerasan Seksual Terhadap Anak di Wilayah Hukum Polres Wajo - YUstiana; Miftahul Khair; Ahmad Fausan; Surianto; Anugrah Saputra (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2026)
The purpose of the study is to provide legal protection for victims of sexual violence against children and to determine the factors that hinder law enforcement against perpetrators of sexual violence against children in the Wajo Police Criminal Investigation Unit. The research method used by the researcher is two methods, namely normative legal research, by taking legal data sources and secondary data, by processing data from primary, secondary, and tertiary legal materials. Data collection tools include library research, as well as qualitative research with field research, through observation and interviews with respondents. The results of the study indicate that legal protection for victims of sexual violence against children, namely legal protection for child victims of sexual violence at the Police (PPA Unit) includes assistance by female police officers (psychologists), identity confidentiality, trauma prevention (child-friendly interviews), and law enforcement based on the TPKS Law No. 12/2022 and the Child Protection Law. These efforts include medical, social assistance, and the right to restitution. The police collaborate with the UPTD PPA, the Social Service, or psychologists to provide assistance during the investigation process for trauma recovery. Factors hindering law enforcement against perpetrators of sexual violence against children at the Wajo Police Criminal Investigation Unit are: Based on a study of law enforcement for sexual violence against children, the main inhibiting factors at the Wajo Police Criminal Investigation Unit generally include internal obstacles (lack of dedicated PPA personnel, limited infrastructure) and external obstacles (victims or families being afraid to report, lack of evidence or witnesses, and efforts to resolve the matter amicably).